The Boolean zeta function - Javtokas, Algirdas (Lietuvos matematikos rinkinys, 2005)
This paper provides analysis on Dirichlet series with an coefficients obtained from MAJm (x1,..., xm) function known in theoretical computer science.
Keywords: Boolean zeta-function; geometric zeta-function; zeta function